Assessing the anticorrosive activity of some organic molecules containing heteroatoms - Chaar,Hamza.; Omar, Falah.; Khachana, Kaiss. (University of Eloued جامعة الوادي, 2025)
Density Functional Theory (DFT) was employed to investigate the global reactivity descriptors and Mulliken charge distribution, along with structure–activity relationship (SAR) analysis and molecular dynamics (MD) simulations. These computational methods were applied to examine how the electronic properties of two compounds namely 2-thiophene carboxylic acid (TC1) and 2-thiophene carboxylic acid hydrazide relate to their effectiveness in inhibiting the corrosion of carbon steel in an acidic environment. The results from the reactivity descriptors, SAR analysis, and MD simulations aligned well with experimental findings, confirming their corrosion inhibition performance. Furthermore, the Mulliken charge analysis provided insight into the reactive sites within the molecules, identifying the atoms most likely involved in electron transfer processesاسخُخذمج وظشيت الكثبفت الىظيفيت ) DFT ( لذساست مُىَصِّفبث الخفبعليت الشبملت وحىصيع شحىبث مىليكه، ببلإضبفت إلى ححليل علالت البىيت ببلىشبط ) SAR ( ومحبكبة الذيىبميكيب الجضيئيت ) MD (. طُبِّمج هزي الطشق الحسببيت لذساست كيفيت اسحببط الخصبئص الإلكخشوويت لمشكبيه، وهمب حمض 2 ثيىفيه الكشبىكسيلي ) - TC1 ( وهيذساصيذ حمض 2 ثيىفيه الكشبىكسيلي، - بفعبليخهمب في حثبيظ حآكل الفىلار الكشبىوي في بيئت حمضيت. ولذ حىافمج وخبئج مُىَصِّفبث الخفبعليت، وححليل علالت البىيت ببلىشبط، ومحبكبة الذيىبميكيبث الجضيئيت بشكل جيذ مع الىخبئج الخجشيبيت، مؤكذةً أداءهمب في حثبيظ الخآكل. علاوةً على رلك، وفّش ححليل شحىبث مىليكه فهمًب أعمك للمىالع الخفبعليت داخل الجضيئبث، مُحذدًا الزساث الخي يُحخمل حىسطهب في عمليبث ومل الإلكخشون.
Master's thesis in chemical engineering
Keywords: DFT; global reactivity parameters; Mulliken charges; SAR; MD; TC1; TC2; وظشيت الكثبفت الىظيفيت، معبملاث الخفبعليت الشبملت، شحىبث مىليكه، SAR ، MD ، TC1 ، TC2 .